Financial integration in ASEAN emerging markets: The relationship between macroeconomic variables and stock index performance from 2011 to 2020 - Dizon, Loren Margaret Malabanan (Animo Repository, 2022)
It is well known that the stock market of a country is important to every nation as it serves as an indicator of their economy. As the ASEAN faces numerous opportunities and challenges, it is identifiable that financial integration within the region is increasing, yet with global financial markets rather than its neighboring countries (Rillo, 2018). This thesis paper aims to identify the relationship between macroeconomic variables and stock market index performance for chosen ASEAN emerging markets in the years 2011 to 2020 to further deepen the understanding of financial integration. The researchers utilized these selected macroeconomic variables: inflation rate, interest rate, economic growth rate, foreign direct investments, and exchange rate to find its relationship with the chosen ASEAN emerging markets which includes Indonesia, Malaysia, Philippines, Thailand, and Vietnam. To achieve the objectives of this study, R Studio was used and utilized the Panel Generalize Method of Moments (GMM) and the Granger Causality Test in order to determine the relationship and impact between the macroeconomic variables and the stock market index performance. As a result in the first model, Interest Rate (IR) and Foreign Direct Investments (logFDI), are the only variables that appeared to have a significant impact, according to the Panel GMM Model Testing. The impact of the exchange rate (ER), foreign direct investments (logFDI), and COVID was also found to be significant in the second model. The researchers have also considered the COVID-19 pandemic and have tested the effect of it towards the stock returns pre and during pandemic. Pre-pandemic resulted that the majority of the returns are positive with little or some negative returns. While during pandemic, this was reciprocated meaning majority of the returns are negative. Furthermore, the researchers also tested the impact of the macroeconomic variables before and during the pandemic towards the returns. Results show that during the COVID-19 pandemic, only two variables have displayed changes: Inflation Rate (INF) which was determined that it has strengthened its negative relationship, while Economic Growth Rate has resulted in a positive relationship with stock market returns (RET). Granger causality, on the other hand, had no significant impact on the variables and are therefore not all granger causal; and, in order to show significant impact, a higher frequency data is needed.